Deterioration of heart rate recovery index in patients after carotid artery stenting. Issue 6 (December 2017) - Aytac, Emrah; Gonen, Murat; Dogdu, Orhan; Balin, Mehmet
Objective: Although carotid artery stenting (CAS) is an effective treatment for severe carotid stenosis, it has been associated with alterations in autonomic functions long term after the procedure. Patients with CAS have been reported to have autonomic nervous system (ANS) dysfunction. This study aimed to evaluate heart rate recovery (HRR) indices and exercise test parameters after CAS. Methods: Patients (10 male, 11 female) suitable for CAS, without a history of hypertension, diabetes mellitus, severe coronary artery or valvular heart disease, were enrolled in our study. Basal electrocardiography, echocardiography, and treadmill exercise testing were performed in all patients pre- and post-procedure. The HRR index was defined as the reduction in the heart rate from the rate at peak exercise to the rate first minute (HRR1 ), second minute (HRR2 ), third minute (HRR3 ) and fifth minute (HRR5 ) after the cessation of exercise stress testing. Results: The exercise time, maximal heart rate, maximal blood pressure and maximal metabolic equivalents values were significantly decreased after the procedure. The first- and second-minute HRR indices of patients before procedure were significantly lower than after procedure (23.5 ± 6.6 vs 25.8 ± 8.3; p  < 0.001 and 41.8 ± 12.3 vs 50.2 ± 16.3; p  < 0.001, respectively). Similarly, HRR indices after the third and fifth minutes of the recovery period were significantly lower in patients before procedure, when compared with those indices after procedure (52.9 ± 13.1 vs 60.7 ± 14.4; p  < 0.001 and 62.4 ± 12.8 vs 71.9 ± 14.1; p  < 0.001). Conclusion: We have demonstrated that HRR indices increased in the first, second, third and fifth minutes of the recovery period after maximal exercise testing in patients after the CAS procedure, which may be a reflection of parasympathetic dominance after CAS.